THE INFLUENCE OF PRODUCTS AND PROMOTIONS ON THE RESILIENCE OF UMKM IN BABAT TOMAN DISTRICT DURING THE COVID-19 PANDEMIC - Dea Okta Viani; Havis Aravik; Choirunnisak (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2022)
This study analyzes the effect of products and promotions on the resilience of UMKM in Babat Toman district during the Covid-19 pandemic. The sample is selected using the saturated sample technique. 51 respondents’ data was collected through documentation and questionnaires. This study implements a multiple linear regression method to analyze the data. The results of the investigation prove that partially the product does not have a significant effect on the resilience of UMKM, while promotion has a significant effect on the resilience of UMKM. But simultaneously products and promotions have a significant effect on the resilience of UMKM.